Inhibition of biofilm formation and preformed biofilm in Acinetobacter baumannii by resveratrol, chlorhexidine and benzalkonium: modulation of efflux pump activity - Migliaccio, Antonella; Stabile, Maria; Triassi, Maria; Dé, Emmanuelle; De Gregorio, Eliana; Zarrilli, Raffaele (Frontiers in Microbiology, 2024)
IntroductionThe persistence of Acinetobacter baumannii in the contaminated environment is sustained by tolerance to biocides and ability to growth as biofilm. The aim of the study was to analyze the susceptibility of A. baumannii biofilms to chlorhexidine (CHX) and benzalkonium (BZK) biocides and the ability of natural monomeric stilbenoid resveratrol (RV) to modulate the phenomenon.MethodsBiofilm formation and preformed biofilm were tested by Crystal violet and tetrazolium salt reduction assay, respectively. Analysis of efflux pump (EP) expression during biofilm growth was performed by Real-time RT-PCR assays.ResultsCHX and BZK at ¼ and ½ MICs alone or in combination inhibited biofilm growth of A. baumannii ATCC 19606, 4190, and 3909 strains. RV at 32 mg/L and CHX and BZK at ¼ or ½ MICs showed a synergistic effect and completely inhibited biofilm formation in all A. baumannii strains. Similarly, RV at 32 mg/L and CHX and BZK at ½ MIC significantly inhibited air-liquid biofilm formation of A. baumannii ATCC 19606, 4190 and 3909 strains. The inactivation of AdeB and AdeJ RND EPs in A. baumannii ATCC19606 increased the susceptibility to CHX and BZK alone or in the presence of 32 mg/L RV. Concordantly, carbonyl cyanide m-chlorophenylhydrazine (CCCP) increased the susceptibility to CHX, BZK and RV and dose-dependently inhibited biofilm formation in A. baumannii ATCC 19606, 4190 and 3909 strains. RV at 32 mg/L inhibited basal and CHX-induced EP genes expression, while increased EP gene expression in the presence of BZK during A. baumannii ATCC19606 biofilm growth. In addition, CHX and BZK alone or in combination dose-dependently reduced preformed biofilm of all A. baumannii strains. The combination of RV with CHX and BZK additively decreased minimal biofilm eradicating concentrations in A. baumannii strains.ConclusionThese results demonstrate that: (i) CHX and BZK alone or in the presence of RV inhibit biofilm growth and preformed biofilm in A. baumannii; (ii) tolerance to CHX and BZK during biofilm growth is dependent on the activation of AdeB and AdeJ EPs; and (iii) the inhibitory effect of RV on biofilm growth is mediated by the inhibition of EP genes expression in A. baumannii.